POLA PERTUKARAN SOSIAL DALAM INTERAKSI ANTARA PEMULUNG DAN AGEN PENJUALAN SAMPAH DI TPA MUARA FAJAR PEKANBARU - Masdelina "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was conducted at the final disposal (TPA) Kecamatan Rumbai of Muara Fajar Pekanbaru with problems: (1) How Sales Agent Profile Trash Scavenger Muara Fajar Di TPA? (2) How to Analyze Social Exchanges Between scavenger with trash in the TPA Dealers Muara Fajar ?. The purpose of this study To Know Sales Agent Profile Waste and TPA Scavengers In Muara Fajar and Explaining Social Exchange Analysis in Social Interaction Between Scavengers and Dealers Garbage in TPA Muara Fajar. This study uses descriptive qualitative research methods, subjects in this study were taken by purposive sampling technique namely those involved in socio-economic relations between the scavenger with sales agents Muara Fajar waste in the TPA. To collect research data using the data in-depth interview guidelines, observation and documentation. The results of this study explains that there are socio-economic relations between sales agent garbage scavengers of these relationships are formed patterns of social exchange is no cost and the rewards received by both. patterns formed more dominant on The proportion Value, Stimulus, Approval-Agresi and Rational. As for the cost they receive their discounted items, delays debt repayments scavengers, while the rewards they receive are always pick-up the goods Pulungan agent scavengers, their sense of shared destiny and arms and thus creating a sense of mutual help between them both in lending and borrowing, as well as a social visit.Keywords: Social Exchange, Social Interaction, Scavengers and Agents